Effect of Work Environment Factors on Willingness to Stay Level - Fildzah Zatalini Zakirah; Hanson Endra Kusuma (ITB Journal Publisher, LPPM ITB, 2021)
The quality of a workspace is influenced by the surrounding environment, called the work environment. A good work environment has a positive influence on comfort and willingness to stay. A comfortable workspace can improve performance and productivity. This study looked at the effect of work environment factors, both physical and non-physical, on someone’s willingness to stay while working in a workspace. This research used qualitative-quantitative methods. Explorative-qualitative methods were used to collect data about the work environment factors. Explanatory quantitative methods were used to see how these work environment factors influence the respondent’s willingness to stay level. Data collection in both stages of the study used an online questionnaire that was distributed freely (non-random sampling). From this study, 11 work environment factors that affect someone’s willingness to stay and intention to move were identified: social interaction, quality of visual interior, natural environment, spaciousness, artificial ventilation, glare, crowd, natural air, facility, air temperature, and humidity. The result of the analysis revealed that there were factors that strongly affect someone’s willingness to stay, factors that weakly affect someone’s willingness to stay, and factors that strongly affect someone’s intention to move.